Sex Differences in Stroke Rehabilitation Care in Alberta. (12th July 2020) - Tanlaka, Eric; King-Shier, Kathryn; Green, Theresa; Seneviratne, Cydnee; Dukelow, Sean
ABSTRACT: Background: Female stroke patients may experience poorer functional outcomes than males following inpatient rehabilitation. Methods: Data from Alberta inpatient stroke rehabilitation units were examined to determine: (1) the impact of sex on time to inpatient rehabilitation, functional gains (using the Functional Independence Measure (FIM)), length of stay (LOS), and discharge destination; (2) if sex was related to age at the time of stroke, stroke severity, and living arrangement at discharge from rehabilitation; and (3) whether patients' age and preadmission living arrangement had an influence on LOS in rehabilitation or discharge destination. Results: Two thousand two hundred sixty-six adult stroke patients (1283 males and 983 females) were subcategorized as mild (FIM >80; n = 1155), moderate (FIM 40–80; n = 994), or severe (FIM <40; n = 117). Fifty-five percent of males (45.7% females) had mild stroke; 39.5% of males (49.5% females) had moderate stroke; and 5.5% of males (4.8% females) had severe stroke. Females were significantly older than males ( p = 2.4 × 10 −4 ). No sex difference existed in time from acute care to rehabilitation admission ( p = 0.73) or in mean FIM change ( p = 0.294). Mean LOS was longer for females than males ( p =0.018). Males were more likely than females to be discharged home ( p = 1.8 × 10 −13 ). Further, male patients ( p = 6.4 × 10 −7 ) and those < 65 years ( p = 1.4 × 10 −23 ) were more likely to be discharged home without homecare. Conclusion: There are significant sex and age differences in LOS in rehabilitation and discharge destination of stroke patients. These differences may suggest that sex and age of the patient need to be considered in care planning.